2022
DOI: 10.1186/s41232-022-00205-x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of SARS-CoV-2 RNA positivity from various specimens and clinical characteristics in patients with COVID-19: a systematic review and meta-analysis

Abstract: Background The duration of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA positivity will be important to prevent the spread of coronavirus disease 2019 (COVID-19). A systematic review and meta-analysis were conducted following PRISMA to determine the duration from several parts of the body and clinical characteristics affecting it. Main text PubMed, Web of Science, Scopus, and CENTRAL were searched for original studies reporting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 117 publications
4
9
0
Order By: Relevance
“…As extensively described for numerous viral infections, both innate immunity and T cell-mediated adaptive immune response are essential for the clearance and long-term inhibition of viral infections [35,36]. It is also important to acknowledge that studies have associated the persistence of SARS-CoV-2 with severity of disease, the presence of comorbidities and use of glucocorticoids [38][39][40][41]. In our series of immunosuppressed patients, all were hospitalized with severe forms of COVID 19.…”
Section: Discussionmentioning
confidence: 91%
“…As extensively described for numerous viral infections, both innate immunity and T cell-mediated adaptive immune response are essential for the clearance and long-term inhibition of viral infections [35,36]. It is also important to acknowledge that studies have associated the persistence of SARS-CoV-2 with severity of disease, the presence of comorbidities and use of glucocorticoids [38][39][40][41]. In our series of immunosuppressed patients, all were hospitalized with severe forms of COVID 19.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the magnitude of viral shedding, studies report high variations of temporal viral shedding patterns among individuals ( He et al, 2020 ; Jones et al, 2021 ; Sun et al, 2022 ). In addition, the duration of viral shedding can be highly heterogeneous, with pooled estimates of mean durations ranging from 11.1 to 30.3 days, and almost all reviews reporting high heterogeneity of estimates ( Cevik et al, 2021 ; Chen et al, 2021b ; Díaz et al, 2022 ; Fontana et al, 2021 ; Li et al, 2020b ; Okita et al, 2022 ; Qutub et al, 2022 ; Rahmani et al, 2022 ; Xu et al, 2020 ; Yan et al, 2021 ; Zhang et al, 2021 ). Such heterogeneities still exist in subgroup analyses by age and severity ( Cevik et al, 2021 ; Fontana et al, 2021 ; Okita et al, 2022 ; Qutub et al, 2022 ; Rahmani et al, 2022 ; Xu et al, 2020 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the duration of viral shedding can be highly heterogeneous, with pooled estimates of mean durations ranging from 11.1 to 30.3 days, and almost all reviews reporting high heterogeneity of estimates ( Cevik et al, 2021 ; Chen et al, 2021b ; Díaz et al, 2022 ; Fontana et al, 2021 ; Li et al, 2020b ; Okita et al, 2022 ; Qutub et al, 2022 ; Rahmani et al, 2022 ; Xu et al, 2020 ; Yan et al, 2021 ; Zhang et al, 2021 ). Such heterogeneities still exist in subgroup analyses by age and severity ( Cevik et al, 2021 ; Fontana et al, 2021 ; Okita et al, 2022 ; Qutub et al, 2022 ; Rahmani et al, 2022 ; Xu et al, 2020 ; Yan et al, 2021 ). The infectious period, proxied by duration of replicant competent virus isolation, is also heterogeneous ( Rahmani et al, 2022 ; Appendix 1—table 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the magnitude of viral shedding, studies report high variations of temporal viral shedding patterns among individuals (38)(39)(40). In addition, the duration of viral shedding can be highly heterogeneous, with pooled estimates of mean durations ranging from 11.1 days to 30.3 days, and almost all reviews report high heterogeneity of estimates identified from literatures (37,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Such heterogeneities still exist in subgroup analyses by age and severity (37,(41)(42)(43)(44)(45)50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the duration of viral shedding can be highly heterogeneous, with pooled estimates of mean durations ranging from 11.1 days to 30.3 days, and almost all reviews report high heterogeneity of estimates identified from literatures (37,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Such heterogeneities still exist in subgroup analyses by age and severity (37,(41)(42)(43)(44)(45)50). Also, the infectious period, proxied by duration of replicant competent virus isolation, is also heterogeneous (50).…”
Section: Discussionmentioning
confidence: 99%